KESETARAAN PERAN GENDER DALAM SERIAL SEX AND THE CITY MUSIM PERTAMA : KAJIAN FEMINISME RADIKAL LIBERTARIAN - Maya Kurnia Dewi (Fakultas Ilmu Budaya, Universitas Dian Nuswantoro, 2012)
Gender does not refer to biogical facts of a man or a woman, but it is rather considered as a social construction toward the roles of a man or a woman. Patriarchal world makes men dominate in public field, while women are seen asdomestic beings. Gender inequality is an ordinal hierarchy between men and women in material resources, power, and status. In discussing this matter, libertarian radical feminism can be used because it discusses gender as the main cause of oppression toward women. One of the TV series discussing the theme is Sex and the City, the First Season. The show follows the lives of a group of four women who are single, successful, and independent. This series changes the view of seeing women’s gender roles as the oppressed side, particularly in sexuality. The power and money that they get make them can treat men as a sexual object.